Pengaruh Pendapatan Asli Daerah (Pad), Dana Alokasi Umum (DAU), Dana Alokasi Khusus (Dak), Dana Bagi Hasil (DBH) Terhadap Pengalokasian Belanja Modal Provinsi Di Indonesia - Irawan, Bobby Andi; , Drs. Agus Endro Suwarno, M.Si (2016)
Condition Capital expenditures in the budget in the provincial government of Indonesia less of attention, the government should be allocated APBD for capital expenditure and not for consumables used for personnel expenditure and current expenditures. Implementation of regional autonomy gives local governments the opportunity to further develop the potential of the region. The purpose of this study was to obtain empirical evidence to determine whether there is influence revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and DBH (DBH) of the Allocation of Capital Expenditure provincial governments throughout Indonesia. In this research a method of the sample used is a technique purposif of sampling , the population in this research was the whole provinces in indonesia years 2013-2014 .This study using secondary data reports in the form of the realization of regional the government of se indonesia years 2013-2014. The test results showed PAD, DAU and DAK are given not positive and significant impact on capital expenditures in the Province of Indonesia, but DBH given significant effect on capital expenditures in the province of Indonesia.